ENGLISH LEARNING ASSISTANCE FOR FOSTER CHILDREN AT AL-JIHAD ORPHANAGE SURABAYA - Tatik Muflihah; Novi Rahmania Aquariza (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2020)
The management of orphanages can be implemented in the form of social services, education, and health. One form of implementation of education conducted in the orphanage Al-Jihad Surabaya in the form of learning assistance for the students. The reason why is mostly students in this orphanage are school-age children. The implementation of this community aims to equip the students with English vocabulary skills. They are guided through learning mentoring activities. This activity was carried out as an effort to motivate students to learn English vocabulary which is one of the key elements of learning foreign language. The method used is to implement learning assistance using flash card media. To know the initial ability of students, they were given pretests in the form of instruction to do some exercises. While, to identify the students’ vocabulary improvement, they were given posttest. Results indicated students’ motivation in learning and vocabulary were improved.